2018
DOI: 10.1002/ddr.21505
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of intestinal and hepatic CYP3A by 1α,25‐dihydroxyvitamin D3: Effects on in vivo oral absorption and disposition of buspirone in rats

Abstract: 1α,25‐Dihydroxyvitamin D3 (also called 1,25(OH)2D3 or calcitriol) is the biologically active form of vitamin D, which functions as a ligand to the vitamin D receptor (VDR). It was previously reported that intestinal cytochrome P450 3A (CYP3A) expression was altered by 1,25(OH)2D3‐mediated VDR activation. However, to clarify whether the change in CYP3A subfamily expression by VDR activation can affect metabolic function, further evidence is needed to prove the effect of 1,25(OH)2D3 treatment on CYP3A‐mediated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
11
0
1
Order By: Relevance
“…In the Caco-2 cells pretreated with VDR ligand drugs containing 1,25(OH) 2 D 3, it was consistently reported the CYP3A4 protein expression level was significantly induced [9], which had been demonstrated that CYP3A4 expression was upregulated by 1,25(OH) 2 D 3 via binding to the specific vitamin D response element (VDRE) [17]. In a recent study, we found the expression and function of intestinal and hepatic CYP3A were differentially changed by 1,25(OH) 2 D 3 treatment in vivo, and that these changes had significant impacts on the oral absorption and disposition of buspirone (a CYP3A substrate drug) in rats [2]. Likewise, the co-administration of ergocalciferol and cholecalciferol markedly reduced the plasma levels of atorvastatin, a CYP3A4 substrate, and its active metabolites in human [18].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the Caco-2 cells pretreated with VDR ligand drugs containing 1,25(OH) 2 D 3, it was consistently reported the CYP3A4 protein expression level was significantly induced [9], which had been demonstrated that CYP3A4 expression was upregulated by 1,25(OH) 2 D 3 via binding to the specific vitamin D response element (VDRE) [17]. In a recent study, we found the expression and function of intestinal and hepatic CYP3A were differentially changed by 1,25(OH) 2 D 3 treatment in vivo, and that these changes had significant impacts on the oral absorption and disposition of buspirone (a CYP3A substrate drug) in rats [2]. Likewise, the co-administration of ergocalciferol and cholecalciferol markedly reduced the plasma levels of atorvastatin, a CYP3A4 substrate, and its active metabolites in human [18].…”
Section: Introductionmentioning
confidence: 92%
“…The dosing solutions were administered intraperitoneally to rats at a dose of 1 mL/kg/day (2.56 nmol/kg/day as 1,25(OH) 2 D 3 ) over four consecutive days. On the fifth day, rats were used for pharmacokinetic study [2,11,12,16,27].…”
Section: 25(oh) 2 D 3 Treatment In Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rats were acclimatized in a clean room of the Laboratory Animal Center of Pusan National University (Busan, Korea) for 1 week. Then, they were fasted for 12 h prior to the pharmacokinetic experiment and then anesthetized by intramuscular injection of Zoletil at a dose of 20 mg/kg [20,21]. The femoral vein and artery of the rats were cannulated with a polyethylene tube (BD Medical; Franklin Lakes, NJ, USA).…”
Section: In Vivo Pharmacokinetic Study In Ratsmentioning
confidence: 99%